Dynamics of Bacterial Communities Mediating the Treatment of an As-Rich Acid Mine Drainage in a Field Pilot - Laroche, Elia; Casiot, Corinne; Fernandez-Rojo, Lidia; Desoeuvre, Angélique; Tardy, Vincent; Bruneel, Odile; Battaglia-Brunet, Fabienne; Joulian, Catherine; Héry, Marina (Frontiers in Microbiology, 2018)
Passive treatment based on iron biological oxidation is a promising strategy for As-rich acid mine drainage (AMD) remediation. In the present study, we characterized (by 16S rRNA metabarcoding) the bacterial diversity in a field-pilot bioreactor treating extremely As-rich AMD in situ, over a six months monitoring period. Inside the bioreactor, the bacterial communities responsible for iron and arsenic removal formed a biofilm (“biogenic precipitate”) whose composition varied in time and space. These communities evolved throughout time from a structure at first similar to the one of the feed water used as an inoculum to a structure quite similar to the natural biofilm developing in situ in the AMD. Over the whole monitoring period, iron oxidizing bacteria always largely dominated the biogenic precipitate, with distinct populations (Gallionella, Ferrovum, Leptospirillum, Acidithiobacillus, Ferritrophicum), whose relative proportions extensively varied among time and space. A spatial structuration was observed inside the trays (arranged in series) composing the bioreactor. This spatial dynamic could be linked to the variation of the physico-chemistry of the AMD water between the raw water entering and the treated water exiting the pilot. According to redundancy analysis (RDA), the following parameters exerted a control on the whole bacterial communities potentially involved in the water treatment process: dissolved oxygen, temperature, pH, dissolved sulfates, arsenic and Fe(II) concentrations and redox potential. Appreciable arsenite oxidation occurring in the bioreactor could be linked to the stable presence of two distinct monophylogenetic groups of Thiomonas related bacteria. The ubiquity and the physiological diversity of the bacteria identified, as well as the presence of bacteria of biotechnological relevance, suggested that this treatment system could be applied to the treatment of other AMD.